Assessment of golf-specific skill performance: a systematic review, 3D visualization, and standardized testing framework - Pan, Xiaoyang; Soh, Kim Geok; Wan Jaafar, Wan Marzuki; Sun, He (Springer Science and Business Media Deutschland GmbH, 2026)
Purpose: Skill testing is a key component of sports science, yet research on golf performance assessment remains limited. This study aims to systematically review existing methods for evaluating golf performance and to visually present their design principles and indicator systems using a 3D bubble chart, ultimately proposing an optimized and standardized testing framework for golf skills. Methods: Following the PRISMA guidelines, this study conducted a systematic search of Web of Science, PubMed, SPORTDiscus, Scopus, and Google Scholar, ultimately including 13 studies for analysis. Results: Combined with 3D visualization indicate that existing research is overly concentrated on driving and putting, while iron and chipping tests are markedly underrepresented, limiting the comprehensive understanding of the four core golf skills. The number of shots and selection of measurement variables lack standardization. Although complex biomechanical and club–ball dynamics indicators can help explain performance mechanisms, overemphasis on these measures often overlooks the core objective of golf—getting the ball into the hole. Conclusion: This study proposes a standardized modular testing framework centered on “target-hitting.” Consists of four modules: ball-striking zone (e.g., grass, bunkers, slopes), target zone (e.g., fairway, green, and varying sizes), shot distance, and club selection. By adjusting the combination of modules, it can simulate complex scenarios and accommodate athletes of different skill levels, providing a scientific reference for research, training, and performance evaluation. This study also provides guidance on the test modules and test site setup.